2015
DOI: 10.1007/s00405-015-3704-8
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid function following total thyroidectomy using energy devices

Abstract: LigaSure precise (LP) and harmonic scalpel (HS) are two energy-based devices used in thyroidectomy surgery. We aimed to compare the effect of these two devices in patients who had undergone total thyroidectomy, by highlighting the post-operative parathyroid function. A total of 201 consecutive patients for whom total thyroidectomy had been planned were prospectively classified into two groups. There were 104 patients in LP group and 97 patients in HS group. Hypoparathyroidism was followed up by serially measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A summary of study characteristics and collected baseline patient variables can be found in Tables 1 and 2 , respectively. 6,8,9,14-33…”
Section: Resultsmentioning
confidence: 99%
“…A summary of study characteristics and collected baseline patient variables can be found in Tables 1 and 2 , respectively. 6,8,9,14-33…”
Section: Resultsmentioning
confidence: 99%
“…Larger vessels would have been tied in most cases; however, more recently devices including Harmonic Scalpel (Ethicon) and LigaSure (Covidien) would have been used in some instances. Some papers have suggested the use of these devices may have an effect on parathyroid function, although no conclusive papers were found to date [18]. Intraoperative factors that have been shown in some series to be associated with increased risk of hypocalcaemia include: number of parathyroids identifies; parathyroids removed; autotransplantation of parathyroid tissue; and longer operative time [4,8,12,14].…”
Section: Factors Not Included In the Analysismentioning
confidence: 94%
“…Due to variations in the parameters used to diagnose hypoparathyroidism, the incidence of hypoparathyroidism after thyroidectomy is variable, it was 5% in a study by Ref. [ 8 ], 1.6–83% [ 9 ], and 1.2–40% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoparathyroidism may be due to accidental parathyroid gland removal or vascular injury [ 9 ] Laboratory assessment of parathyroid function includes PTH and serum ca level [ 9 ].…”
Section: Discussionmentioning
confidence: 99%